INTERNATIONAL LEGAL FEATURES OF THE DISSOLUTION OF THE MARITAL RELATIONSHIPS (Journal of actual problems of jurisprudence, 2018)
This article is devoted to analysis of the decision of international legal conflicts that arise from divorce with a foreign element. As well as the issues of legal regulation of these relations in accordance with the legislation of the Republic of Kazakhstan. The authors of the article examined in detail the provisions of the CIS Convention on Legal Assistance and Legal Relations in Civil, Family and Criminal Matters 1993, Convention on the Law Applicable to Matrimonial Property Regimes of 1978, The Hague Convention on the settlement of conflicts of laws and jurisdiction over divorce and legal separations, as well as the Convention on the Nationality of Married Women 1957. Moreover, there is studied the experience of the law of foreign countries of Europe and Latin America and of individual States on this issue. Key words: Convention, marital relationships, dissolution of marriage, property rights of spouses, conflict rules, domestic laws, norms of the international Treaty, family, citizens of the Republic of Kazakhstan, a foreign citizen.